Business students’ perspectives: What makes successful group performance? - Rinny Cherill Rantung; Reggy Nelson Sarmita (International Journal of Evaluation and Research in Education (IJERE), 2020)
Purpose of this study was to identify factors contributing to the successful group performance from the perspective of business students. The in-depth interview was done followed by a survey derived forty-five items variables, after some tests 21 items variables removed due to low item remainder coefficient resulted in 24 items questionnaires. A total of 355 respondents participated during the survey. Exploratory factor analysis with principal factor extraction was performed and five contributing factors were extracted. Those factors are cohesiveness, inter-relationship, norms, diversity and appointed of team leader.